2020
DOI: 10.3390/ijms21186701
|View full text |Cite
|
Sign up to set email alerts
|

Anti-PD-1 Therapy Does Not Influence Hearing Ability in the Most Sensitive Frequency Range, but Mitigates Outer Hair Cell Loss in the Basal Cochlear Region

Abstract: The administration of immune checkpoint inhibitors (ICIs) often leads to immune-related adverse events. However, their effect on auditory function is largely unexplored. Thorough preclinical studies have not been published yet, only sporadic cases and pharmacovigilance reports suggest their significance. Here we investigated the effect of anti-PD-1 antibody treatment (4 weeks, intraperitoneally, 200 μg/mouse, 3 times/week) on hearing function and cochlear morphology in C57BL/6J mice. ICI treatment did not infl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 62 publications
0
4
0
Order By: Relevance
“…ABR tests were performed to follow up changes in auditory function by measuring hearing thresholds as previously described [ 9 , 51 ]. In brief, mice were anesthetized with a mixture of ketamine-xylazine injection (100 mg/kg and 10 mg/kg, intraperitoneally, respectively).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…ABR tests were performed to follow up changes in auditory function by measuring hearing thresholds as previously described [ 9 , 51 ]. In brief, mice were anesthetized with a mixture of ketamine-xylazine injection (100 mg/kg and 10 mg/kg, intraperitoneally, respectively).…”
Section: Methodsmentioning
confidence: 99%
“…Underlying factors of cochlear aging include genetic susceptibility, otological disorders, and environmental factors, for example, increased noise exposure [ 5 , 6 ]. The main pathological processes presumed to play a crucial role in the development of ARHL are ischemia, excitotoxicity [ 6 ], increased level of reactive oxygen species (ROS) [ 7 ], apoptosis [ 8 ], and low-grade inflammation [ 9 , 10 ]. As a result, age-related degeneration of stria vascularis, auditory hair cells (HCs), and spiral ganglion neurons (SGNs) could be primarily observed [ 6 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…As such, it is plausible that the mechanism through which these checkpoint inhibitors cause inner ear damage is through disruption of the melanocytic cells within the inner ear, similar to the rare autoimmune disorder Vogt‐Koyanagi‐Harada syndrome 11 . Other work has suggested that the outer hair cells may be affected at the basal turn of the cochlea in animal models 12 …”
Section: Methodsmentioning
confidence: 99%
“…11 Other work has suggested that the outer hair cells may be affected at the basal turn of the cochlea in animal models. 12 The next point worth noting regarding these nonplatinum-based ototoxic agents is that the majority of these studies were published within the last 15 years (after 2005). Interestingly, many of the agents and classes of drugs over this recent history include chemo-and immunotherapeutics agents.…”
Section: Summary Of Findingsmentioning
confidence: 99%